2022
DOI: 10.1080/07420528.2022.2040527
|View full text |Cite
|
Sign up to set email alerts
|

Association of delayed chronotype with allergic diseases in primary school children

Abstract: Has your child ever been diagnosed with asthma? □ yes □ no 2.Has your child experienced any wheezing, breathing difficulties, or whistling in the chest in the last 12 months? □ yes □ no 3.Has your child ever been diagnosed with allergic rhinitis? □ yes □ no 4.Has your child ever sneezing, runny nose, stuffy, or itchy in the last 12 months not due to having a cold or flu? □ yes □ no 5.Has your child had repeated skin itching or a rash on the bent side of the elbow or knee joint in the last 12 months? □ yes □ no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…A new study from India identified the association between chronotype (individual preference for morningness or eveningness) and allergic conditions including asthma. This is the first report on this topic that demonstrated an association between more eveningness and a higher risk of asthma and allergic diseases in children, 25 which was subsequently supported by several other studies, including in adults 36–40 . Therefore, prospective studies focusing on these issues could be important to identify more non‐conventional risk factors for allergic diseases in the Indian population.…”
Section: Risk Factors – What Is Novel In Indiasupporting
confidence: 57%
See 2 more Smart Citations
“…A new study from India identified the association between chronotype (individual preference for morningness or eveningness) and allergic conditions including asthma. This is the first report on this topic that demonstrated an association between more eveningness and a higher risk of asthma and allergic diseases in children, 25 which was subsequently supported by several other studies, including in adults 36–40 . Therefore, prospective studies focusing on these issues could be important to identify more non‐conventional risk factors for allergic diseases in the Indian population.…”
Section: Risk Factors – What Is Novel In Indiasupporting
confidence: 57%
“…Smoking inside the house is a big problem in Indian societies and is significantly associated with a higher prevalence of asthma and allergic diseases among Indian children 29 . Lifestyle factors such as more evening activities and higher screen timing are also associated with higher risks of asthma and allergic diseases in children 25,36–40 . All these factors play substantial roles in the diagnosis, treatment, and prognosis of chronic allergic diseases in India, particularly in children.…”
Section: Pitfalls and Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Finally, a study by Chen et al (2022) that sampled Chinese children from ages 7-12 showed that children without eczema slept an average of 9.53 hr per night, while children with eczema slept an average of 9.42 hr per night ( P < .001). 21 …”
Section: Resultsmentioning
confidence: 99%
“…20 Finally, a study by Chen et al (2022) that sampled Chinese children from ages 7-12 showed that children without eczema slept an average of 9.53 hr per night, while children with eczema slept an average of 9.42 hr per night (P < .001). 21 Decreased sleep efficiency. Sleep efficiency is commonly defined in the literature as the ratio of total sleep time to the total time spent in bed, expressed as a percentage.…”
Section: Delayed Sleep Onsetmentioning
confidence: 99%